Main Conditions of Development of Agro-industrial Complex of Ukraine on an Innovation Basis Основные условия развития агропромышленного комплекса Украины на инновационной основе - Tsygan Raisa N. (Bìznes Inform, 2013)
The article is devoted to solution of the existing problems of innovation development of the agro-industrial complex of Ukraine. The authors make a conclusion that permanent and continuous innovation development of the agro-industrial complex is one of the most important components of prosperity and effectiveness of agricultural production. The article identifies main conditions of innovation development of agriculture in Ukraine. It justifies significance of completion of the land reform and creation of the land market; financing the agro-industrial complex; and development of scientific and technical activity. It states that wide application of innovations is the most effective means of solution of socio-economic tasks of the agro-industrial complex. It concludes that further research should be directed at the search for new innovation approaches in managing agricultural companies. Статья посвящена решению существующих проблем инновационного развития агропромышленного комплекса Украины. Авторы делают вывод, что постоянное и непрерывное инновационное развитие АПК является важнейшей составляющей процветания и эффективности сельскохозяйственного производства. В статье определены основные условия инновационного развития сельского хозяйства Украины. Обосновано значение завершения земельной реформы и создания рынка земли; финансирования агропромышленного комплекса; развития научно-технической деятельности. Широкое применение инноваций является наиболее действенным и эффективным средством решения социально-экономических задач АПК. В дальнейшем исследование необходимо направлять на поиск новых инновационных подходов в управлении сельскохозяйственными предприятиями.